Inovasi Web-Based System untuk Karang Taruna Aceh Meningkatkan Efisiensi dan Akses Informasi - Fahmi, Rahmad (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2025)
Karang Taruna organization as a forum for developing the younger generation has an important role in improving the social welfare of the community. However, along with the development of the era, the need for an efficient and integrated information system is increasingly urgent. This study aims to design and implement Web-Based System Innovation for Karang Taruna Aceh to Increase Efficiency and Access to Information. This system is designed to facilitate data management, increase transparency, and expand access to information for Karang Taruna members and the general public. The research method used is the waterfall model, which includes the stages of needs analysis, system design, implementation, testing, and evaluation. This system is developed with web-based technology to ensure wide accessibility and ease of use. The results of the study show that this system is able to increase the efficiency of data management, accelerate the distribution of information, and support Karang Taruna activities in a more structured manner. With this system, it is hoped that Karang Taruna Aceh can be more optimal in carrying out its role as a forum for developing the younger generation and empowering the community. This study also contributes to the application of information technology for community organizations, especially in the increasingly developing digital era.